2021
DOI: 10.1128/jcm.01062-21
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variations in Test Reactivity for the Serological Diagnosis of Trypanosoma cruzi Infection

Abstract: Chagas disease is a neglected disease caused by Trypanosoma cruzi parasites. Most of diagnosis is based on serological tests but the lack of a gold standard test complicates the measurement of test performance. To overcome this limitation, we used samples from a cohort of well-characterized T. cruzi infected women to evaluate the reactivity of two rapid diagnostic tests and one ELISA assay. Our cohort derived from a previous study on congenital transmission of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Here we only note that the large fraction of false positive obtained with the Hemagen ELISA placed a large burden on EBNHC staff who had to ensure confirmatory testing at the CDC. We do not know in what way our patients’ test results were affected by the significant variations in sensitivity of Chagas serologic testing recently noted in dependence on patients’ geographic region of origin [ 28 , 29 ]. Truyens and colleagues found that the sensitivity of the ELISA they examined varied between 89.7 and 27.9% [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here we only note that the large fraction of false positive obtained with the Hemagen ELISA placed a large burden on EBNHC staff who had to ensure confirmatory testing at the CDC. We do not know in what way our patients’ test results were affected by the significant variations in sensitivity of Chagas serologic testing recently noted in dependence on patients’ geographic region of origin [ 28 , 29 ]. Truyens and colleagues found that the sensitivity of the ELISA they examined varied between 89.7 and 27.9% [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite sustaining "hundreds" of bites from triatomines over a 10-year period, frequently finding them inside his home, and evidence of T. cruzi-infected triatomines collected from inside the home, our patient did not have clinical or serological evidence of chronic CD. There has been some concern that certain T. cruzi DTU strains found within certain geographic regions in Mexico, as well as Central and South America, have discordant serological testing results [29][30][31][32]. The sensitivity and specificity of our available CD serological tests have not been assessed among those with autochthonous CD in the US at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient did have an HIV infection and was adherent to ART with sustained viral suppression and normal CD4 counts. Chagas disease among those with uncontrolled HIV/AIDS can lead to significant reactivation of T. cruzi and often times will be fatal [32,33]. Despite having CD4 counts greater than 200, T. cruzi DNA can still be detected in the blood of those infected with HIV, which likely indicates those living with HIV are at continued risk for reactivation Chagas disease [34].…”
Section: Discussionmentioning
confidence: 99%
“…The ABBOTT and Bio-Rad tests are commonly used serological tests for T. cruzi infection. Considering the variability by location of tests' performance [20][21][22], this in-house ELISA was chosen as a screening method because its antigens were grown using local parasite strains, as detailed below.…”
Section: Methodsmentioning
confidence: 99%
“…However, many of these tests are not readily available in most clinical settings [19]. Furthermore, many serological tests have been shown to perform differently in different geographic regions, in Mexico and across other Latin American countries [20][21][22].…”
Section: Diagnosis Of CDmentioning
confidence: 99%